Unraveling Side Reactions in the Photocatalytic Reduction of CO2: Evidence for Light‐Induced Deactivation Processes in Homogeneous Photocatalysis. Issue 4 (15th January 2015) - Meister, Simon; Reithmeier, Richard O.; Tschurl, Martin; Heiz, Ueli; Rieger, Bernhard
Abstract Photocatalytic reduction of CO2 with rhenium(I) bipyridine complexes has been studied for several decades. Nonetheless, important parameters affecting the catalytic performance remain elusive to date. By using the standard catalyst [Re(dmb)(CO)3Cl] (dmb=4, 4′‐dimethyl‐2, 2′‐bipyridine), the effect of catalyst concentration and irradiation intensity is studied in detail and important correlations are revealed. The decomposition of the catalyst is investigated, and two main deactivation pathways are proposed, both of which involve the one‐electron‐reduced species and are likely to be valid for other homogeneous photocatalysts as well. The rate of deactivation is linked to the relative concentration of 1) the catalyst in its electronic ground state, 2) the catalyst in its excited state, 3) the one‐electron‐reduced species, and 4) quencher radicals. Adequate tuning of catalyst concentration and irradiation intensity leads to the highest quantum yield (Φ=0.53) reported to date for a single‐molecule system.